2014
DOI: 10.3390/nano4010157
|View full text |Cite
|
Sign up to set email alerts
|

Percolation Diffusion into Self-Assembled Mesoporous Silica Microfibres

Abstract: Percolation diffusion into long (11.5 cm) self-assembled, ordered mesoporous microfibres is studied using optical transmission and laser ablation inductive coupled mass spectrometry (LA-ICP-MS). Optical transmission based diffusion studies reveal rapid penetration (<5 s, D > 80 μm2∙s−1) of Rhodamine B with very little percolation of larger molecules such as zinc tetraphenylporphyrin (ZnTPP) observed under similar loading conditions. The failure of ZnTPP to enter the microfibre was confirmed, in higher resoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 54 publications
(70 reference statements)
0
22
0
2
Order By: Relevance
“…In a first experiment, we assembled Cy5‐MSN‐3@RhB particles that were loaded with RhB but lacked the aptamer gatekeeper (Figure A). Imaging of RhB fluorescence revealed that the dye, due to its small size (9.8 Å × 4.3 Å × 15 Å) can freely diffuse from the particle's pores and is taken up by the adhered cells. In contrast, patterns containing Cy5‐MSN‐3‐Apt@RhB particles, which were capped with the gatekeeper, did not release their RhB cargo, as indicated by the absence of RhB fluorescence inside the cells (Figure B).…”
Section: Cargo‐loaded Msn Patternsmentioning
confidence: 99%
“…In a first experiment, we assembled Cy5‐MSN‐3@RhB particles that were loaded with RhB but lacked the aptamer gatekeeper (Figure A). Imaging of RhB fluorescence revealed that the dye, due to its small size (9.8 Å × 4.3 Å × 15 Å) can freely diffuse from the particle's pores and is taken up by the adhered cells. In contrast, patterns containing Cy5‐MSN‐3‐Apt@RhB particles, which were capped with the gatekeeper, did not release their RhB cargo, as indicated by the absence of RhB fluorescence inside the cells (Figure B).…”
Section: Cargo‐loaded Msn Patternsmentioning
confidence: 99%
“…Self‐assembly of monodispersed SiO 2 nanoparticles with the size of 20–30 nm resulted in formation of a densely packed monolithic structure containing discrete mesospaces (2–6 nm) among the particles by convective flow through evaporation . The mesospaces can immobilize Rhodamine B, zinc porphyrins, and also even entire enzymes . The uniform mesoporous structure of SiO 2 nanoparticles is suited for incorporation of PtNPs without agglomeration during the catalytic reaction .…”
Section: Immobilization Of Photosynthetic Reaction Centers and Model mentioning
confidence: 99%
“…[163] The mesospaces can immobilize Rhodamine B, zinc porphyrins, and also even entire enzymes. [163][164][165] The uniform mesoporouss tructure of SiO 2 nanoparticles is suited for incorporation of PtNPs withouta gglomeration during the catalytic reaction. [166] Al 3 + -dopedS iO 2 nanoparticles with the size of 20-30 nm (Al-SiO 2 NPs) were prepared by surfacea lumination of SiO 2 NPs with NaAlO 2 in an aqueous dispersion.…”
Section: Redox Photocatalysis Of Rc Modelcompoundsmentioning
confidence: 99%
“…The effective diffusion coefficient of rhodamine B across the polycarbonate membrane was estimated to quantify the membrane permeability. Rhodamine B was chosen due to its fluorescent characteristics and because its molecular size (about 16 Å) is close to the that of most of the nutrients present in the culture medium (size of glucose 8.6 Å) . The glucose diffusion was not determined, but its diffusion was qualitatively checked across the membrane, as presented in the Supporting information (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that effective diffusion of rhodamine occurs, with diffusion coefficient of (D rho,eff ) 3.3 × 10 −9 cm 2 s −1 and permeability 6.60 × 10 −6 cm s −1 (Supporting information S3.1). Mcdonagh et al . estimated the diffusion coefficient of rhodamine B in self‐assembled, ordered mesoporous microfibres using optical transmission and laser ablation inductive.…”
Section: Resultsmentioning
confidence: 99%